2015
DOI: 10.3390/medsci3040112
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Potential of the Polysaccharide-Rich Extract from Edible Cyanobacterium Nostoc commune

Abstract: A dry sample of Nostoc commune from an organic farm in Pingtung city (Taiwan) was used to prepare polysaccharide-rich (NCPS) extract. The conditioned medium (CM) from NCPS-treated human peripheral blood (PB)-mononuclear cells (MNC) effectively inhibited the growth of human leukemic U937 cells and triggered differentiation of U937 monoblast cells into monocytic/macrophagic lines. Cytokine levels in MNC-CMs showed upregulation of granulocyte/macrophage-colony stimulatory factor and IL-1β and downregulation of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
7
0
3
Order By: Relevance
“…Moreover, the polysaccharide is mostly β -1, 3 and β -1, 4 glycoside bonds, which are not easy to be absorbed by the intestinal tract, and it has strong moisture absorption, moisture retention, and high relative viscosity [ 9 , 13 , 14 ]. Studies have shown that NSKP has rich biological activities, including anti-inflammatory and lipid-lowering effects [ 15 17 ]. However, there are a few studies on moistening intestines and the laxative effect of NSKP.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the polysaccharide is mostly β -1, 3 and β -1, 4 glycoside bonds, which are not easy to be absorbed by the intestinal tract, and it has strong moisture absorption, moisture retention, and high relative viscosity [ 9 , 13 , 14 ]. Studies have shown that NSKP has rich biological activities, including anti-inflammatory and lipid-lowering effects [ 15 17 ]. However, there are a few studies on moistening intestines and the laxative effect of NSKP.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Nostoc is an edible, largely consumed cyanobacterial form after Spirulina. Polysaccharide-rich extracts of Nostoc commune could be potentially used for macrophage activation and consequently inhibit the leukemic cell growth and induce monocytes/macrophages when used to treat human monoblastoid leukemia U937 cells [73]. Different immunomodulating activities of Microcystis aeruginosa, Synechocystis aquatilis, Oscillatoria redekei, Anabaena flos-aque, Aphanizomenon flos-aquae, Oscillatoria rubescens, Oscillatoria tenuis have also been reported [74] their different cell extracts variably promote the proliferation of lymphocytes.…”
Section: Immunomodulatory and Anti-inflammatory Effectsmentioning
confidence: 99%
“…There is one major thing that all the polymers have in common: the higher amount of 1,3 substituted glucose units [ 11 ]. Liao et al also reported the immunomodulatory potential of the polysaccharide-rich extract from N. commune (NCPS) and found that the immunity of murine macrophage Raw 264.7 cells might be activated by nitric oxide and superoxide secretion and consequently effectively inhibit the growth of human leukemic U937 cells as well as trigger the differentiation of U937 monoblast cells into monocytic/macrophagic lines resulting from the upregulation of GM-CSF and IL-1β as well as the downregulation of IL-6 and IL-17 [ 65 ]. Taken together, these studies demonstrated that N. commune may have potential as a cancer chemopreventative agent.…”
Section: Anti-carcinogenic and Immunomodulatory Properties Of mentioning
confidence: 99%